2008
DOI: 10.1111/j.1468-2885.2008.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication Network Evolution in Organizational Communities

Abstract: Organizational communities are typically defined as populations of organizations that are tied together by networks of communication and other relations in overlapping resource niches. Traditionally, evolutionary theorists and researchers have examined organizational populations that comprise organizational communities by focusing on their properties rather than on the networks that link them. However, a full understanding of the evolution of organizational communities requires insight into both organizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 84 publications
0
89
1
Order By: Relevance
“…In addition, it is not uncommon to observe that existing nodes and edges are eliminated and dissolved over time, which in turn leads to the structural change of the network in different ways from those that the previous models predict. Especially when it is costly to maintain connections, so that the maximum number of edges that a node can carry is bounded (i.e., relational carrying capacity; Monge, Heiss, & Margolin, 2008), the formation of edges would be inevitably selective. Generally speaking, the addition of nodes and the formation of edges in a given network are subject to certain selection mechanisms, as the growth of species in a given environment is constrained by the pressure of natural selection.…”
Section: Recent Developments In Network Researchmentioning
confidence: 99%
“…In addition, it is not uncommon to observe that existing nodes and edges are eliminated and dissolved over time, which in turn leads to the structural change of the network in different ways from those that the previous models predict. Especially when it is costly to maintain connections, so that the maximum number of edges that a node can carry is bounded (i.e., relational carrying capacity; Monge, Heiss, & Margolin, 2008), the formation of edges would be inevitably selective. Generally speaking, the addition of nodes and the formation of edges in a given network are subject to certain selection mechanisms, as the growth of species in a given environment is constrained by the pressure of natural selection.…”
Section: Recent Developments In Network Researchmentioning
confidence: 99%
“…For example, relations that involve the exchange of resources and knowledge among sectors are the norm and certainly the latest trend in successful social service models (Chen et al, 2012;Gulati & Singh, 1998;Isett & Provan, 2005;Kapucu, 2005;Mandell, 2001;Monge, Heiss, & Margolin, 2008;Westley & Vredenburg, 1997). Networks of community organizations working for a common purpose are thought to increase community capacity to meet social needs (Monge, Heiss, & Margolin, 2008;Parker & Selsky, 2004;Westley & Vredenburg, 1997). The benefits of interorganizational networks include (a) bringing diverse groups and resources together, and (b) addressing issues that no group can resolve by itself (Witte, Reinicke, & Benner, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adding a new perspective to this longstanding debate, Monge, Heiss, and Margolin (2008) have suggested that it would be beneficial to switch focus from traits of types to their network properties as the basis for defining evolving populations: "Traditionally, evolutionary theorists and researchers have examined organizational populations that comprise organizational communities by focusing on their properties rather than on the networks that link them. However, a full understanding of the evolution of organizational communities requires insight into both organizations and their networks."…”
Section: Introductionmentioning
confidence: 99%